Extending the temporal context of ethnobotanical databases: the case study of the Campania region (southern Italy) - Pollio Antonino; Pezzatti Gianni; De Natale Antonino (BMC, 2009)
Abstract Background Ethnobotanical studies generally describe the traditional knowledge of a territory according to a "hic et nunc" principle. The need of approaching this field also embedding historical data has been frequently acknowledged. With their long history of civilization some regions of the Mediterranean basin seem to be particularly suited for an historical approach to be adopted. Campania, a region of southern Italy, has been selected for a database implementation containing present and past information on plant uses. Methods A relational database has been built on the basis of information gathered from different historical sources, including diaries, travel accounts, and treatises on medicinal plants, written by explorers, botanists, physicians, who travelled in Campania during the last three centuries. Moreover, ethnobotanical uses described in historical herbal collections and in Ancient and Medieval texts from the Mediterranean Region have been included in the database. Results 1672 different uses, ranging from medicinal, to alimentary, ceremonial, veterinary, have been recorded for 474 species listed in the data base. Information is not uniformly spread over the Campanian territory; Sannio being the most studied geographical area and Cilento the least one. About 50 plants have been continuously used in the last three centuries in the cure of the same affections. A comparison with the uses reported for the same species in Ancient treatises shows that the origin of present ethnomedicine from old learned medical doctrines needs a case-by-case confirmation. Conclusion The database is flexible enough to represent a useful tool for researchers who need to store and compare present and previous ethnobotanical uses from Mediterranean Countries.